2011
DOI: 10.1080/10937404.2011.578564
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Signaling as a Common Target of Organohalogens and Other Neuroendocrine Disruptors

Abstract: Organohalogen compounds such as polychlorinated biphenyls (PCB) and polybrominated diphenyl ethers (PBDE) are global environmental pollutants and highly persistent, bioaccumulative chemicals that produce adverse effects in humans and wildlife. Because of the widespread use of these organohalogens in household items and consumer products, indoor contamination is a significant source of human exposure, especially for children. One significant concern with regard to health effects associated with exposure to orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 298 publications
0
10
0
Order By: Relevance
“…A single paper also suggests that long-term exposure to chlorobenzenes (solvents) may also disrupt neurohypophysial AVP and OT release (149). Complementary work by multiple research teams has identified NO signaling as a potent target of many EDCs including PBDEs, PCBs, and other organohalogens (representative examples include (74, 150, 151)) suggesting another possible route by which EDCs could impact AVP function. Concomitant work focused on the parvocellular aspects of AVP signaling has also found evidence of NO endocrine disruption by GEN, BPA, and other EDCs (39, 74, 151).…”
Section: Avp Impacts—beyond Brain and Behaviormentioning
confidence: 99%
“…A single paper also suggests that long-term exposure to chlorobenzenes (solvents) may also disrupt neurohypophysial AVP and OT release (149). Complementary work by multiple research teams has identified NO signaling as a potent target of many EDCs including PBDEs, PCBs, and other organohalogens (representative examples include (74, 150, 151)) suggesting another possible route by which EDCs could impact AVP function. Concomitant work focused on the parvocellular aspects of AVP signaling has also found evidence of NO endocrine disruption by GEN, BPA, and other EDCs (39, 74, 151).…”
Section: Avp Impacts—beyond Brain and Behaviormentioning
confidence: 99%
“… sexual behaviour and neural circuits related to its control are more sensitive endpoints than others currently used in toxicological studies (70, 71); neuropeptides and enzymes are major targets for the action of EDCs in the vertebrate brain (72); among different peptidergic systems kisspeptin in rodents (73–77), vasotocin in birds (48, 78, 79), as well as the enzyme aromatase in fishes (80–82), or the enzyme NO‐synthase in rodents (83, 84), appear to be the most sensitive to low levels of EDCs during early development; alterations of these circuits may induce profound effects on sexual behaviour (85), puberty (74), reproductive physiology (86) and feeding behaviour (87); neural circuits can be altered also at synaptic levels, for example, in the hippocampus (63, 88–90), and have profound effects on learning and memory (91); the putative mechanisms of action needs to be more thoroughly explored (69) but, in addition to EDCs binding to steroid or thyroid hormone receptors, they include the aryl hydrocarbon receptor, its interactions with ERβ, the activation of the P450 cytochromes, which are involved in the metabolism of most steroid hormones, the peroxisome proliferator‐activated receptor γ and retinoid receptors important in adipose tissue. …”
Section: Brain and Behaviour Targets For The Endocrine Disruptersmentioning
confidence: 99%
“…among different peptidergic systems kisspeptin in rodents (73–77), vasotocin in birds (48, 78, 79), as well as the enzyme aromatase in fishes (80–82), or the enzyme NO‐synthase in rodents (83, 84), appear to be the most sensitive to low levels of EDCs during early development;…”
Section: Brain and Behaviour Targets For The Endocrine Disruptersmentioning
confidence: 99%
“…These modes of action include (1) altered intracellular calcium homeostasis (Inglefield et al, 2001), (2) modulation of PKC (Kodavanti and Ward, 2005), (3) altered glutamate neurotransmission (Mariussen and Fonnum, 2001), and (4) decreased levels of neurotransmitters such as dopamine (Seegal et al, 2002) and serotonin (Khan and Thomas, 2004) in rodent brain. Increasing evidence suggests that nitric oxide (NO) signaling might also be disrupted by PCBs and other endocrine disrupting chemicals (EDCs, Sharma and Kodavanti, 2002;Martini et al, 2010;Currá s-Collazo, 2011). NO which is produced by nitric oxide synthase (NOS), is a gaseous neurotransmitter that serves an important role in neuroendocrine function (Garthwaite and Boulton, 1995), in synaptic processes associated with learning and memory such as a retrograde messenger underlying long term potentiation (LTP), (Bohme et al, 1991;O'Dell et al, 1991;Schuman and Madison, 1991), and in neurodegeneration (Liberatore et al, 1999;Palumbo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%